A diktatúra szép kerek világa az NDK és a keletnémetek a szocialista blokkban - Slachta Krisztina (Aetas, 2021)
The GDR had a unique position among the countries of the Eastern Bloc, as its history was always more connected to the FRG than its fellow Socialist countries. The emigration problem constantly plaguing the GDR had always determined its self-definition and political communication, and the problem continued even after the building of the Wall. The aging population also led to ever increasing labour and skill shortages in the country. The solution came in the form of labour exchange contracts with other Socialist countries, which also involved student exchange. However, expanding connections to even countries within the bloc were not without risks for Eastern Germany. By the mid-1980s the leadership of the GDR also lost its trust in the Hungarian system, as more and more press releases, diplomatic and state security reports indicated changes, economic transformation, and ongoing reform processes in Hungary.